2019
DOI: 10.1063/1.5052194
|View full text |Cite
|
Sign up to set email alerts
|

Field-free spin-orbit torque switching of a perpendicular ferromagnet with Dzyaloshinskii-Moriya interaction

Abstract: Field-free spin-orbit torque switching of a perpendicular ferromagnet with Dzyaloshinskii-Moriya interaction. Applied Physics Letters, 114(2), article no. 022401. For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 45 publications
7
30
0
Order By: Relevance
“…We note that this value is very close to the absolute value of applied in-plane H ex (−20 Oe, see Fig. 3b ) where magnetization switching vanishes, which is consistent with the hypothesis that the g-DMI-induced effective field is responsible for the observed field-free switching 33 35 .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…We note that this value is very close to the absolute value of applied in-plane H ex (−20 Oe, see Fig. 3b ) where magnetization switching vanishes, which is consistent with the hypothesis that the g-DMI-induced effective field is responsible for the observed field-free switching 33 35 .…”
Section: Resultssupporting
confidence: 89%
“…The DMI effect can induce spin textures (e.g., domain walls and skyrmions) with broken chiral symmetry 29 – 32 . Therefore, DMI has recently been theoretically proposed as a symmetry-breaking mechanism that, in combination with damping-like and field-like SOTs, may enable deterministic switching in the absence of an external field 33 35 . However, field-free deterministic switching due to the combined action of DMI and SOT has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been shown that the Dzyaloshinskii-Moriya Interaction (DMI) is playing an important role in SOT switching [17,18] as well as domain wall motion [19]. The chiral effective field arises from DMI at the FM and HM interfaces, along with the spin polarized current, may contribute to the deterministic field-free switching of a perpendicularly magnetized FM layer [18,[20][21][22]. Furthermore, Slonczewski-like (damping-like) torque (SLT or DLT) has been mainly used to analyze the SOT switching and domain wall dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…DMI favors the chiral magnetic textures (e.g. spin spirals, skyrmions, and Neel type domain walls) and dramatically affects the magnetization dynamics, as validated by the recent studies [14][15][16][17][18][19][20][21][22][23][24][25]. It is important to mention that the role of the DMI will become more complicated in the double-interface MTJ, since two FM/HM interfaces need to be considered together with an additional RKKY interaction.…”
Section: Introductionmentioning
confidence: 79%